Alignment of business and social media strategies: insights from a text mining analysis. (3rd July 2018) - Hassan Zadeh, Amir; Jeyaraj, Anand
ABSTRACT: Organisations utilise social media technologies for various customer engagement and external-facing activities in recent years. This research examines the extent to which the business strategies and social media strategies of organisations are aligned. Using a sample of 33 organisations competing in the information technology industry, the business strategies were operationalised using data extracted from the annual 10-K reports while the social media strategies were identified from the Twitter feeds. Topic modelling with latent semantic analysis revealed six different orientations in the business and social media strategies of organisations, which were used to evaluate alignment. This study also identified clusters of organisations with varying levels of alignment. Implications for research and practice are discussed.